Symmetry dual functional pyrimidine-BODIPY probes for imaging targeting and activity study - Xu, Shuping; Liu, Ying; Wang, Zhou; He, Aolin; Jin, Guofan (Frontiers in Chemistry, 2022)
Nondestructive diagnosis of tumor has always been the goal of scientists. Fluorescent dyes have become the rising star in the field of cancer diagnosis because of their excellent characteristics. Therefore, in this work, fluorescence probes d-Y-B and dO-Y-B with anti-tumor activity were constructed by introducing pyrimidine groups with high anti-tumor activity using fluorescence dye BODIPY as parent nucleus. The modified BODIPY group in the structure had the advantage of fluorescent dye, ensuring the strong fluorescence and photosensitivity of the target compound. That ethylenediamine acts as a bridge with two -NH- groups to increase molecular hydrogen bonding, and can bind firmly to multiple proteins. Co-localization of the target compounds d-Y-B and dO-Y-B with the hoechst dye for labeling living cells showed that these compounds had high biocompatibility and photostability for localization to HeLa cells. In vivo imaging in mice can realize specific localization and real-time visualization of tumor cells. The results of cytotoxicity experiments in vitro and computer software simulating molecular docking confirmed the potential of the target compounds as an anticancer agents. The bifunctional probe realized visualization of cancer cells in mice, and can kill cancer cells by anti-proliferation, which may provide a direction for future anticancer drug development.